Desain Pembelajaran Pecahan Menggunakan Konteks Bendungan Watervang - Sukasno; Zulkardi; Putri, Ratu Ilma Indra; Somakim (Jurnal Pendidikan Matematika RAFA, 2024)
The purpose of this study is to produce students' learning trajectories in studying addition and subtraction of fractional numbers. The operation of adding and splitting fractional numbers is one of the materials that must be mastered by elementary school students. The learning approach used is the Indonesian Realistic Mathematics Education (PMRI) approach with the context of the Watervang dam. The use of the Watervang dam context is used as a means to apply the concept of addition and subtraction of fractional numbers to real problems. His research uses the validation studies type design research method. The subjects of the study were six grade IV students of SD IT An-Nida Lubuklinggau City. This research produces a learning trajectory (LT) which contains a series of learning activities that help students understand the concepts of addition and subtraction of fractional numbers. Based on the results of the study, it was found that the learning trajectory using the context of the Watervang dam can help students develop an understanding of the concept of addition and subtraction of fractional numbers.